Individualised Professional Development Using the Pyramid Model in an Urban Head Start Programme. Issue 3 (4th May 2021) - Green, Katherine; Robbins, Sandra; Varga, Mary; Head, Cynthia; Davis, Erin; Houze, Whitney
ABSTRACT: In the United States, preschool teachers report behaviour management as one of the greatest challenges when educating young children. Teachers consistently feel unprepared to meet the needs of children with persistent challenging behaviours. Unfortunately, the issue affects more than just preschool teachers. Behaviour issues that emerge in preschool, if left unaddressed, can become chronic by third grade. Fifty percent or more of preschoolers who exhibit challenging behaviours continued to have these challenges in upper grade levels. Sixty-six percent of that 50% have been diagnosed with 'attention deficit hyperactivity, oppositional defiant behavior, or conduct disorder by age nine' (Zaghlawan & Ostrosky, p. 439). These ongoing challenging behaviours have a negative impact on academic outcomes including maths, reading, and vocabulary skills. Moreover, chronic challenging behaviours that go unresolved in the early years, have been shown to negatively impact developmental trajectories, leading to peer rejection, academic failure, failure to graduate high school, and unemployment. For these reasons and more, there has been an increased emphasis in the last decade on identifying evidence-based practices that address challenging behaviours and promote social-emotional competence among preschool children (e.g.; Domitrovich, Moore, & Greenberg, 2012).